(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Optic atrophy refers to the death of the retinal ganglion cell axons that comprise the optic nerve, and manifests on fundoscopy as a pale optic nerve. Optic atrophy is the end stage of myriad causes of optic nerve damage anywhere along the path from the retina to the lateral geniculate. Since the optic nerve transmits retinal information to the brain, optic atrophy is associated with vision loss. However, the term "atrophy" is somewhat of a misnomer as it implies disuse; thus, this optic nerve damage is better termed "optic neuropathy."